Bimbingan Konseling dalam Peningkatan Kualitas Belajar Mahasiswa Perguruan Tinggi Islam Negeri - Imron Mustofa; Moch. Kalam Mollah (Indonesian Journal of Islamic Education Studies (IJIES), 2019)
Social pressure and great desire to take education at level of the State Islamic University (PTAIN) has given rise to several challenges. This paper elaborates some problems experienced by students of PTAIN. This paper approach is field research with literature data (library research) as support material. The paper concludes college has unique characteristics, self-reliance and mental-spiritual balance. In progress, there are two problems faced by students of PTAIN: personal and social issues (non-academic). Both come down to mindset and mental conditions. They give depth impact on life management, adjustments to academic world, environment and society. Not a few students experience introvert attitude and new environment makes them uncomfortable, eventually lead to saturation.